Detection of inhomogeneities in biological tissues using radio wave tomography. (October 2019) - Eremeev, A I; Shipilov, S E
Abstract: The paper shows the method for detecting and mapping inhomogeneities in biological tissues with using the radio-wave tomosynthesis. The method of radio-wave tomosynthesis allows calculating a three-dimensional distribution of permittivity in a studying space. The distribution gives the opportunity to determine tissue inhomogeneities, also their location and size. This method is suitable for dynamic observation of changes in education size due to harmlessness to humans. Unlike X-ray methods, for which regular doses of ionizing radiation contraindicated. Therefore, the development of non-invasive methods for the search for inhomogeneities in biological media based on radio-wave sounding is very relevant.